Germination, vigour and dormancy of sunflower seeds following chemical desiccation of female plants - Szemruch, Cyntia; Renteria, Santiago; Moreira, Fabiana; Cantamutto, Miguel; Ferrari, Liliana; Rondanini, Deborah (Seed Science and Technology, 2014)
The aim of this study was to analyse the impact of chemical desiccation on (i) the germination and vigour of seeds of contrasting sunflower genotypes, and (ii) the level of seed dormancy, with emphasis on the anatomical characteristics of seed coverings. Two treatments were applied, at 30% seed moisture content: (i) spraying plants with paraquat and (ii) detaching seed heads. Control untreated plants remained in the field until 10% seed moisture was reached. Seed dormancy (without pretreatment), germination (after applying one of three dormancy breaking treatments: pre-chilling, pericarp removal, pericarp + seed coat removal) and vigour (by electrical conductivity) were analysed. Chemical desiccation advanced harvest time by 35 - 43 days, increased seed dormancy and improved germination and vigour. Pericarp and seed coat removal had the greatest effect on overcoming dormancy. The outer cell wall thickness of the endospermatic cell layer of the seed coat was associated with dormancy level for the desiccation treatments.
Keywords: Germination; vigour; Dormancy; Sunflower; Chemical desiccation